2021
DOI: 10.3389/fmats.2021.768877
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Capacity of Hollow GFRP Pipe-Concrete-High Strength Steel Tube Composite Long Columns Under Eccentrical Compression Load

Abstract: To investigate the bearing capacity of the hollow Glass Fiber Reinforced Polymer (GFRP) pipe-concrete-steel tube composite long columns subjected to eccentrical compression load, 33 hollow GFRP pipe-concrete-steel tube composite long columns have been designed. The slenderness ratio (λ), compressive strength of concrete cube (fcu), eccentricity (e) and so on are the main parameters. Based on constitutive models for steel, GFRP and confined concrete, numerical simulation of the hollow GFRP pipe-concrete-high st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The study on the bearing behavior of hollow CFDST specimens is carried out by adopting the ultimate equilibrium method [23], and the calculation expression of the axial compression bearing capacity (N u c1 ) is obtained by introducing the constraint effect coefficient (ξ), as shown in Equation (7):…”
Section: The Expression Of the Axial Compression Bearing Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The study on the bearing behavior of hollow CFDST specimens is carried out by adopting the ultimate equilibrium method [23], and the calculation expression of the axial compression bearing capacity (N u c1 ) is obtained by introducing the constraint effect coefficient (ξ), as shown in Equation (7):…”
Section: The Expression Of the Axial Compression Bearing Capacitymentioning
confidence: 99%
“…Therefore, it has become a key problem to realize the reconstruction of adding stories around the existing buildings without interrupting their function [4]. A novel assembled composite frame, consisting of different strength concrete filled double skin steel tube (CFDST) columns and H-shaped honeycombed composite beams with rectangular concrete filled steel tube (RCFST) flanges, is proposed in this paper [5][6][7][8][9]. Both the columns and beams are connected together through integral joints.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional geometric models of square steel tubes, unequal height steel beams, and core confined concrete are created as shown in Figure 3. The eight-joint hexahedral element type C3D8H is used to simulate square steel tubes, unequal height steel beams, and core confined concrete [26,27]. The nonlinear symmetrical contact between the steel tube and concrete is simplified as normal hard contact and tangential friction contact.…”
Section: Finite Element Modeling 221 Establishment Of Parts and Conta...mentioning
confidence: 99%
“…In 2020, Tests and FE analysis on ultra-HPC-filled round high-strength steel tube composite stub columns subjected to axial load were conducted by Wei et al (2019),and the results showed that highstrength steel tubes provided more effective restraint for ultra-HPC, so high-strength steel tube was a better match with ultra-HPC. In 2021, FE analysis on the bearing capacity of hollow GFRP pipe-concrete-steel tube composite long columns subjected to eccentrical load was carried out by Ji et al (2021d), and the results showed that with the increasing of thickness of GFRP tube, steel tube, and cubic compressive strength of concrete, the ultimate eccentrical compression bearing capacity increased gradually, finally a formula for the bearing capacity of such composite columns under eccentrical load was proposed by statistical regression.…”
Section: Introductionmentioning
confidence: 99%